New management approaches and sustainability: the case of the Museo del Traje in Madrid - Ayala, Íñigo (Cultural Trends, 2024)
Times have changed and museums are adapting to it. Their traditional functions have evolved, and the sustainability of these institutions is becoming increasingly important. Therefore, museums are facing a paradigm shift: from heritage-focused to society, especially their audiences. These institutions must now foster and develop social and economic approaches to adapt to this new situation. Cultural democracy and audience development are emerging as an effective approach and management tool in this adaptation process. This research focuses on the case of the Museo del Traje of Madrid [Costume Museum] in Madrid. Through the study of the Museum's website on its activity and in-depth interviews, this article gathers the information analysed to highlight the effort made by this museum in terms of sustainability through its face-to-face activities. The conclusions reveal that despite the efforts made by the museum in its adaptation process, a new management approach is needed to enhance this work. In this way, by improving its management, the Museo del Traje can become a replicable model of a museum that works to promote sustainability.
Keywords: cultural democracy; audience development; Museo del Traje de Madrid; sustainable museums; sustainable development goals